Parent Relationship Satisfaction and Reflective Functioning as Predictors of Emotional Availability and Infant Behavior - Salo Saara J.; Pajulo Marjukka; Vinzce Lazlo; Raittila Simo; Sourander Johanna; Kalland Mirjam (SPRINGER, 2022)
Marital and parenting systems are likely to interact during the first year of an infant's life. This study examines the longitudinal interrelations of relationship satisfaction and parental reflective functioning (PRF) and their predictive relations with later emotional availability (EA) and infant social-emotional behaviors (SEB) including skills as well as behavioral problems among first-time Finnish mothers and fathers (n = 556). The follow-up period was between three and 12 months. In addition to having direct effects, we examined a mediational model in which self-reports on PRF factors of interest and curiosity and appropriateness of reasoning would mediate the effects of previous relationship satisfaction to the parent and dyadic side of EA and infant SEB at 12 months. The results show significant stability for relationship satisfaction and PRF for both mothers and fathers as well as direct effects on EA and SEB. However, we found differences between mothers and fathers. For mothers, path analysis indicated support for a mediational model where earlier relationship satisfaction predicted later EA and infant problem behaviors also through the current level of PRF. For fathers, both relationship satisfaction and PRF had direct, but not mediated, effects, and on both infant problem behaviors as well as infant social competence. Together, despite these differences, focusing clinically on both relationship satisfaction and PRF may prove significant in preventing later relational and/or infant difficulties in SEB for both mothers and fathers.